Analisis Ekologis Meiofauna Sebagai Bioindikator Di Pesisir Pantai Losari, Makassar - Yusal, Muh Sri; Marfai, Muh Aris; Hadisusanto, Suwarno; Khakhim, Nurul (Fakultas MIPA UNM, 2018)
Abstract. The research aims to analyze ecological value of meiofauna as bioindicator in Losari Coast, Makassar. The total meiofauna abundance was 66791 indv/m2, consisted of 12 phylum and 91 species/genus. The stations located at the mouth of the Jeneberang River, Tanjung Merdeka, and the Tallo River are research sites with high levels of abundance, due to the presence of organic contaminants produced by surrounding anthropogenic activity that trigger high growth of meiofauna. ostracoda, oligochaeta, tunicata and ciliophora are the phylum with high levels of abundance compared to other meiofauna, as it that phylum has a high adaptability to the entry of pollutant material in the water. Diversity index and evenness indicates the meioufauna in the Losari Coast categorized by a high level of diversity and evenly distributed. While dominance index indicated that no dominant meifauna species, except at research stations located around the Losari Beach reclamation project. Keywords: Abundance, meiofauna, anthropogenic, Coastal Losari Beach, Makassar